Empowering privacy in the connected home: communal use of smart technologies - Krämer, MJ (2022)
The latest wave of internet-connected smart home technologies promises convenience and control over a diverse network of different systems, such as appliances, utilities, and entertainment devices. Striking the balance between convenience and control proves to be a minefield for product designers. Firstly, the data needs of these technologies amplify concerns over improper data collection and processing practices, highlighting a power imbalance between users and manufacturers. Secondly, convenience and control favour specific practices of use that manifest in related power differentials among household members. Additionally, devices are sometimes utilised for coercive control or domestic abuse.